2020
DOI: 10.3390/s20102902
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Sensor-Based Methodology for the Quantitative Assessment and Classification of Chronic Non Specific Low Back Patients (NSLBP) in Clinical Settings

Abstract: The successful clinical application of patient-specific personalized medicine for the management of low back patients remains elusive. This study aimed to classify chronic nonspecific low back pain (NSLBP) patients using our previously developed and validated wearable inertial sensor (SHARIF-HMIS) for the assessment of trunk kinematic parameters. One hundred NSLBP patients consented to perform repetitive flexural movements in five different planes of motion (PLM): 0° in the sagittal plane, as well as 15° and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…They were also able to classify them according to the risk of chronicity [12]. Similar results with lower accuracy were obtained with the same test but using classical statistical analysis (linear discriminant analysis) [41]. In our study, we found that the SENS2 had higher discriminating power in both classical statistical analysis and ML analysis.…”
Section: Discussionsupporting
confidence: 82%
“…They were also able to classify them according to the risk of chronicity [12]. Similar results with lower accuracy were obtained with the same test but using classical statistical analysis (linear discriminant analysis) [41]. In our study, we found that the SENS2 had higher discriminating power in both classical statistical analysis and ML analysis.…”
Section: Discussionsupporting
confidence: 82%
“…The ability to maintain stability and balance to prevent falls in the elderly is critical. It is not surprising that many studies have identified lower back muscle weakness and balance problems (66,67) as the most important risk factors for falls (68). Furthermore, in COPD patients, the relationship between different components of balance and falling has been well investigated (29)(30)(31).…”
Section: Balance Deficitsmentioning
confidence: 99%
“…A Support Vector Machine classifier methodology was utilized for data classification, which enabled the distinction between the two groups with high accuracy and sensitivity. More recently, smart wearables and sensor-based methodologies have yielded encouraging results for the quantification and classification of LBP ( Davoudi et al, 2020 ). These novel technologies, along with big data management tools (AI, ML, SVM, etc.)…”
Section: Introductionmentioning
confidence: 99%